Validitas Lembar Kerja Peserta Didik Berbasis Penemuan Terbimbing dalam Upaya Meningkatkan Pemahaman Konsep dan Kemampuan Penalaran Matematis - Aan Putra; Hendra Syarifuddin; Zulfah Zulfah (Edumatika : Jurnal Riset Pendidikan Matematika, 2018)
Learning equipment is important things that determine the quality of the learning process and output. We need a study about validity, practicality, and effectiveness of the learning equipment to ensure teaching and learning quality. The purpose of this research is to evaluate the validity of the learning equipment based on guided discovery, especially the students’ worksheets. This research was a descriptive qualitative research that provides the result of students’ worksheets and experts' recommendations. The experts who validated these student’s worksheets were three experts on mathematics education. The instruments used in this study was the validation sheets for LKPD. The result of validation sheets analysis for LKPD showed that in general, the students’ worksheets were valid. The validity of the didactical aspect and contents aspect sequently were 0,667 dan 0,704.